Construction of a prognostic model for colorectal cancer liver metastasis based on single-cell transcriptomics and regulation of the MIF pathway - Cao, Jianqiang; He, Zhaobin; Gao, HuiJie; Yu, Yongzhe; Yang, Shengbiao; Wang, Xiqiang; Niu, Jun; Peng, Cheng (Frontiers in Oncology, 2025)
IntroductionColorectal cancer is associated with a generally poor prognosis, primarily due to its often late diagnosis and the high propensity for liver metastasis. Current treatment strategies emphasize personalized approaches, integrating advanced targeted therapies based on specific molecular profiles to enhance outcomes. Continued research into molecular targets and innovative treatments is crucial for improving survival rates and managing disease progression.MethodsWe retrieved single-cell transcriptomic and bulk RNA-seq data from colorectal cancer samples in the GEO and TCGA databases. The analysis focused on changes in pathway and gene expression in epithelial cells during the metastatic progression. A prognostic risk model was developed based on differentially expressed genes, and experimental validation confirmed the differential expression of prognostic-related genes in colorectal cancer tissues.ResultsDuring the process of liver metastasis in colorectal cancer, the interaction between MIF and its receptors, CD74 and CXCR4, is markedly intensified, promoting tumor cell invasion and migration. The expression levels of TPM2, RPS17, and TNNT1 were significantly elevated, while SPINK4 expression was reduced in the epithelial cells of colorectal cancer with liver metastasis. These findings were further validated experimentally. A prognostic model based on these genes predicted patients’ overall survival at 1, 3, and 5 years.DiscussionDuring liver metastasis in colorectal cancer, the expression levels of TPM2, RPS17, and TNNT1 were significantly elevated, SPINK4 expression was reduced in the epithelial cells. Furthermore, the interaction between the MIF pathway and its ligands, CD74/CXCR4, may play a important role in promoting tumor metastasis.